Analisis Proses Rekrutmen dan Seleksi Karyawan Pada PT. Bakrie Sumatera Plantations Tbk Ditinjau dari Perspektif Islam - Muhammad Fikri Adrian; Tuti Anggraini (Jurnal Informatika Ekonomi Bisnis, 2023)
The purpose of this study was to determine the employee recruitment and selection process carried out by PT Bakie Sumatera Plantations from an Islamic perspective. The research method used is descriptive qualitative. Retrieval of data obtained using interview techniques and field observations. The implementation of the recruitment and selection carried out by PT Bakrie Sumatera Plantations prioritizes the capabilities of prospective employees. The method used by PT Bakrie is also in accordance with Islamic principles which use an open system by using social media and cooperation with the Department of Labor as information dissemination. The nepotism that was carried out at PT Bakrie was based on the ability of prospective employees with a record of passing the tests determined by the company.